Struggle and Survive: Difficulties Encountered by Students Undertaking Research - Evangelista, Lucille; Hernandez, Maria Theresa (Social Sciences and Development Review, 2017)
This study aimed to find out the perception of the respondents on the importance of undertaking research, and the difficulties encountered by undergraduate students in doing research in terms of the following stages: (i) preparing the proposal, (ii) conducting the research, and (iii) writing the research paper, and to determine the measures undertaken to pursue research despite the difficulties encountered in the aforementioned stages. The researchers utilized the descriptive method with a self-constructed questionnaire as the main data gathering instrument. The respondents were 103 College of Arts and Sciences fourth year students who have already taken Research 101 and 102, and are done with their final thesis defense. Data gathered were tabulated and analyzed using relative frequency and weighted mean. Based on the data gathered, the composite mean of 4.41 revealed that undergraduate students perceived research to be a vital component of their academic endeavor during college. They agreed that they encountered difficulties in writing the proposal, conducting the research, and writing the research paper. This was shown with composite means of 4.09, 3.89, and 4.01, respectively. Respondents likewise agreed that measures were taken to pursue writing the proposal, conducting the research, and writing the research paper, with weighted means of 4.29, 4.12, and 4.19, respectively. These findings led the researchers to conclude that research is perceived to be an important undertaking in an undergraduate student’s stay in college.
Keywords: undergraduate research; study; writing research paper; conduct of research; difficulties